1984
DOI: 10.1161/01.res.54.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture measurement of lung microvascular pressure profile during hypoxia in cats.

Abstract: To determine the lung microvascular pressure profile during hypoxia, we micropunctured the subpleural microcirculation of isolated perfused cat lungs. Our procedures involved exsanguinating a cat, then cannulating its pulmonary artery, left atrium, and trachea. Using the cat's own blood, we perfused the lungs at pulmonary artery and left atrial pressures of 18 and 9 cm water, respectively, to obtain lung blood flow of 81 +/- 29 ml/(kg body weight x min), which we held constant throughout the experiment. We sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 19 publications
2
48
0
2
Order By: Relevance
“…9 Ventilation of intact lungs with a hypoxic gaseous mixture (eg, fraction of inspired oxygen=0.10) leads to acute pulmonary vasoconstriction throughout the pulmonary vascular bed, including nonmuscular arterioles, capillaries, and veins, but is most pronounced in small pulmonary arterioles. [10][11][12][13] That said, HPV is not distributed evenly throughout the lung and lung perfusion is inhomogeneous during hypoxia.…”
Section: Pulmonary Arteriolar Vasoconstriction Dominates the Acute Pumentioning
confidence: 99%
“…9 Ventilation of intact lungs with a hypoxic gaseous mixture (eg, fraction of inspired oxygen=0.10) leads to acute pulmonary vasoconstriction throughout the pulmonary vascular bed, including nonmuscular arterioles, capillaries, and veins, but is most pronounced in small pulmonary arterioles. [10][11][12][13] That said, HPV is not distributed evenly throughout the lung and lung perfusion is inhomogeneous during hypoxia.…”
Section: Pulmonary Arteriolar Vasoconstriction Dominates the Acute Pumentioning
confidence: 99%
“…Because of the close agreement Drzcgs and che/nicals. The following drugs and chemicals were between Pdo and microvascular pressure determined by microused: DMTU (Aldrich Chemical Co., Milwaukee, WI) was dis-puncture (10) or by the isogravimetric technique (1 I), Pdo is solved in sterile isotonic saline on the day of each experiment. taken as an estimate of microvascular pressure.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it has been reported that exposure of animals to chronic or acute hypoxia increases plasma ANP concentration up to 2 10-fold (20,21) and that chronic hypoxia decreases the left atrial ANP mRNA level (13). Although the mechanism of hypoxia-induced release of ANP is unclear, pulmonary hypoxic vasoconstriction and change in the pulmonary circulation may be implied (22)(23)(24). From these findings, we consider that the morphine-induced increase in plasma ANP concentration is most likely re lated to respiratory depression and possibly a change in pulmonary circulation, and that in creased ANP release may secondarily enhance the ANP gene expression in the right auricle.…”
Section: Methodsmentioning
confidence: 99%